2022
DOI: 10.3390/rs14246375
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Urban Forest Characteristic Parameters Using UAV-Lidar Coupled with Canopy Volume

Abstract: The estimation of characteristic parameters such as diameter at breast height (DBH), aboveground biomass (AGB) and stem volume (V) is an important part of urban forest resource monitoring and the most direct manifestation of the ecosystem functions of forests; therefore, the accurate estimation of urban forest characteristic parameters is valuable for evaluating urban ecological functions. In this study, the height and density characteristic variables of canopy point clouds were extracted as Scheme 1 and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A higher LAI indicates enhanced utilization of light energy by plants, leading to improved growth conditions and increased aboveground biomass (AGB). According to Zhang et al [29], the incorporation of a canopy structure variable in the ULS-based AGB estimation model for urban forests resulted in enhanced accuracy in various models. Breast diameter estimation was conducted by Xiong et al [95] using UAV-LiDAR to extract tree height and crown diameter, which were then utilized in a binary heteroscedastic growth equation for estimating the most suitable aboveground biomass (AGB) method for individual trees (R 2 of 0.77, RMSE of 15.99 kg).…”
Section: Feature Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher LAI indicates enhanced utilization of light energy by plants, leading to improved growth conditions and increased aboveground biomass (AGB). According to Zhang et al [29], the incorporation of a canopy structure variable in the ULS-based AGB estimation model for urban forests resulted in enhanced accuracy in various models. Breast diameter estimation was conducted by Xiong et al [95] using UAV-LiDAR to extract tree height and crown diameter, which were then utilized in a binary heteroscedastic growth equation for estimating the most suitable aboveground biomass (AGB) method for individual trees (R 2 of 0.77, RMSE of 15.99 kg).…”
Section: Feature Screeningmentioning
confidence: 99%
“…This has attracted a large number of scholars to use LiDAR to carry out forest AGB research [27], such as Mariano et al [28], who explored the AGB estimation model construction method based on LiDAR height, intensity, or a combination of height and intensity data. Zhang et al [29] also accurately and successfully estimated the AGB of the urban forest based on the UAV-LiDAR and coupled it with the structural characteristics of the canopy.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the UAV-LiDAR and backpack-LiDAR data acquisition, 113 Metasequoia plants in the study area were measured and located in this study. The diameter at 1.3 m was measured with a diameter-checking steel ruler, and the height of the tree was measured using a Blume-Leiss height gauge, while the position of the single tree was also accurately located using a Huace Smart RTK (better than 0.5 m accuracy) [22,35]. The statistical characteristics of the field-measured data are shown in Table 2.…”
Section: Field Inventory Datamentioning
confidence: 99%
“…The acquisition of forest parameters with spatial location information is a prerequisite for measuring and evaluating the spatial structure of forests. However, related studies around the world have shown that most forest parameters are obtained through manual field surveys, which have disadvantages such as low efficiency, high cost, and small scale [21,22]. It is therefore important for forest resource monitoring and management to minimize the time and labor costs of field surveys while achieving accurate estimates of forest parameters and their structures [23].…”
Section: Introductionmentioning
confidence: 99%
“…These solutions can be deployed to manage tree stands by monitoring individual trees. Individual trees are identified and modeled with the use of remote sensing methods that rely on point clouds of airborne LiDAR and TLS data [35,36], as well as multispectral photogrammetric data [6,[37][38][39]. Different subsets of the dataset describing individual trees are created through splitting to generate 3D models of dendrological objects [40][41][42][43][44][45] or even to identify tree species [46].…”
Section: Introductionmentioning
confidence: 99%